FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS SISWA (STUDI EMPIRIS PADA SISWA SMK GAMALIEL 1 MADIUN) - Kurniawati, Dyah (Widya Warta, 2017)
The aim of this research was to analyze the impact of satisfaction, trust and perceived value of the commitment and quality of service. The population in students SMK Gamaliel 1 Madiun using stratified sampling. The results showed satisfaction and trust variables significant positive effect on the commitment being perceived value does not affect the commitment. Variable trust and commitment and significant positive effect on loyalty, while the variable quality of service, satisfaction and perceived value has no effect on loyalty.